Recent literatures of the Holocaust: negotiations with (post) memory and the archive - Frost, Helen Dorothy (My University, 2010)
Abstract The primary aim of this dissertation is to investigate the manner in which certain examples of post-Holocaust second and third generation literature negotiate questions of memory, history and the archive, when writing about the Holocaust from a specific spatial and temporal remove. This is undertaken via close readings of three texts, namely: Maus by Art Spiegelman, Austerlitz by Sebald and Everything is Illuminated by Jonathan Safran Foer. Each text required a slightly different theoretical approach and exhibits a different set of subject positions, however they all share the characteristics of generic blurring, self-conscious narration and intertextuality and use these to dramatise their own provisionality. I make specific use of Marianne Hirsch’s term postmemory alongside various theories of the archive including Derrida’s Archive Fever in order to describe these texts’ relation to a remote past. In particular I analysed Maus in terms of postmemory, while considering Spiegelman’s complex visual palimpsest as an archive. Austerlitz was analysed via conceptions of the uncanny and a Derridian elaboration of the concept of the spectre. With specific reference to the inclusion of photographs in the text I show how the spectre of the Holocaust comes to haunt the text, allowing the author to reference it indirectly. Everything is Illuminated, which I believe is an under-theorised text, was analysed in terms of its epistolary structure and its engagement with silence and absence in order to analyse the expression of postmemory from the additional temporal remove of the third generation. Using Hal Foster’s view of the archival impulse expressed in certain art forms I conclude that these texts exhibit an archival approach to the events of the past. I argue that in highlighting its own provisionality each text avoids expressing an authoritative version of the past, and thus avoids the destruction of the heterogeneity of the archival trace.